Wild Animals I Have Known - Seton, Ernest Thompson, 1860-1946 (Salt Lake City, UT : Project Gutenberg, 2002)
"Wild Animals I Have Known" by Ernest Thompson Seton is a collection of short stories published in 1898. This pioneering work of realistic wild-animal fiction depicts predators and other creatures as compassionate, individualistic beings rather than objects or demons. Beginning with "Lobo the King of Currumpaw," based on Seton's wolf-hunting experiences, the stories portray animals as characters with depth and emotion. The book became immensely popular, though it later sparked the nature fakers controversy when critics accused Seton of fabricating animal behaviors and founding an overly sentimental genre. (This is an automatically generated summary.)
Lobo, the King of Currumpaw -- Silverspot, the Story of a Crow -- Raggylug, the Story of a Cottontail Rabbit -- Bingo, the Story of My Dog -- The Springfield Fox -- The Pacing Mustang -- Wully, the Story of a Yaller Dog -- Redruff, the Story of the Don Valley Partridge
Wikipedia page about this book: https://en.wikipedia.org/wiki/Wild_Animals_I_Have_Known
Release date is 2002-01-01
Produced by David Reed, and David Widger
Keywords: Animals -- Biography; Animals -- Anecdotes